Navigating tumour microenvironment in endometrial carcinoma: a comprehensive review integrating immunohistochemistry, single-cell RNA-sequencing and spatial transcriptomics - Mondal, Oishee; Kiruba, Blessy; Sudhakaran, Sajitha Lulu; Sundararajan, Vino (Frontiers in Oncology, 2025)
Endometrial cancer is regarded as one of the most prevalent malignancies in women globally. Despite the advancements brought by multiple therapeutic strategies, the efficacy and effectiveness of treatment still appear to be diminished. Therefore, this accentuates the importance of understanding the tumour microenvironment (TME). Conventional methods, including immunohistochemistry (IHC), along with recently emerged techniques like single-cell RNA sequencing (scRNA-seq) and spatial transcriptomics (ST), have rejuvenated the notion of deciphering TME. From deconstructing tumour heterogeneity, identifying cell populations that play significant roles in treatment response, to discovering key biomarkers and therapeutic targets, these technologies lay the base for innovations. Importantly, this is the first comprehensive review that brings together scRNA-seq, ST, and IHC in Endometrial cancer. Merging these methods is geared towards creating a better grasp of the dynamics and interactions between diverse cells and the TME.